PENGARUH LEVERAGE DAN ARUS KAS OPERASI TERHADAP PERSISTENSI LABA PADA PERUSAHAAN MANUFAKTUR - Monika Angelina; Estralita Trisnawati (Jurnal Paradigma Akuntansi, 2023)
This research aims at how the role of the leverage and operating cash flow on earnings persistence in manufacturing companies listed on the Indonesia Stock Exchange during 2018-2020. Sample was selected using purposive sampling method and obtained 83 companies. Data processing techniques using multiple regression analysis what helped by using Eviews Version 9.5. The results of this study indicate that leverage has a positive and significant effect while operating cash flow has a negative and significant effect on earnings persistence. The implication of this research is the need for the role of earnings persistence in increasing leverage and operating cash flow to provide benefits for the company in generating good profits.